Market Discipline, Information Processing, and Corporate Governance - Martin Hellwig (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
The paper reviews and assesses our understanding of the notion of 'market discipline' in corporate governance. It questions the wholesale appeal to this notion in policy discussion, which fails to provide an account of the underlying mechanisms in terms of theory and empirical analysis. Discipline that is provided by the 'market' must be compared to discipline that is provided by other institutions, e.g., intermediaries acting as 'delegated monitors'. The comparative assessment depends on (i) the information technology, (ii) the role of strategic interactions, and (iii) the disciplinary mechanism itself. Concerning (i), the question is whether the benefits of multiple sources of information exceed the costs. Concerning (ii), strategic interactions concern the free-rider problem in acquiring information that benefits all financiers, as well as distributive externalities involved in exploiting an information advantage to the detriment of other financiers. Concerning (iii), the question is whether investors have explicit intervention rights or whether 'discipline' results from managerial acquiescence. As for the acquisition and aggregation of information in organized markets, positive welfare effects arise only if the information is put to productive use, either through improvements in real investment and managerial incentives, or through changes in corporate control. Necessary conditions for such benefits to arise are fairly restrictive, especially if the changes that occur are based on managerial acquiescence rather than the legal intervention rights of investors. The expansion of market-based managerial incentives in the nineties had little to do with these theoretical accounts. The experience of moral hazard that has accompanied this expansion, on the side of gate-keeping institutions as well as corporate management, confirms the predictions of theory about the potential for shortfalls in market discipline and the agency costs of equity finance through the open market.
urn:nbn:de:bvb:19-epub-13396-3
Keywords: G14; G20; G30; 330; Market Discipline; Financial Institutions; Information Processing; Corporate Governance